Alloys and Composites Corrosion and Mechanical Properties (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This topic aims to provide new research results on the composition design of alloys, material processing technology, novel composites, and coatings in order to improve the corrosion resistance and mechanical properties of ocean materials to meet the extreme marine environment. As is well known, with the development and exploration of marine resources and marine new energy, the research on underwater robots, submarines, and marine new energy equipment is increasing. However, high-performance materials are necessary for the safe service of marine equipment, which constrains the development of marine equipment. For example, for steel structure submarines, their working environment covers corrosive areas of the ocean (atmospheric area, splash area, tidal range area and full immersion area, etc.) and involves interaction with multiple strong fields such as the fluid field, temperature field, stress field and electromagnetic field. The issues of corrosion, fatigue and other failure behaviors in shell, frame, pipeline and other parts result in a decrease in the strength of the steel structure, and can even lead to accidents. Therefore, research studies on the corrosion behavior and protection methods of high-performance alloys and composite materials are becoming more and more important. This topic thus includes the following themes: corrosion property, biofilm, coating, wear, fatigue mechanics, plasticity, alloys, composite, mechanical properties and processing techniques.